2020
DOI: 10.1016/j.mex.2020.100995
|View full text |Cite
|
Sign up to set email alerts
|

Naturally present metal ions in plants could interfere with common antioxidant assays

Abstract: Most of the commonly applied assays used to assess antioxidant properties of plant extracts exploit the ability of some biologically active metabolites to participate in oxidation-reduction reactions with metal ions. On the other hand, most plants contain different chelated metal ions whose levels depend on the geographic origin, soil, and environmental pollutions. In this study the levels of redox-active metal ions in three plant sources were measured and extracts of these botanicals were treated with Chelex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In particular, phenolics exhibit strong antioxidant properties based on their substantial free radical scavenging power [ 2 ]. Additionally, their ability to chelate transitional metals has been widely recognized [ 3 ]. Due to the high concentration of rosmarinic and caffeic acids, lemon balm may be a more efficient source of antioxidants than other food products, which are present on a market.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, phenolics exhibit strong antioxidant properties based on their substantial free radical scavenging power [ 2 ]. Additionally, their ability to chelate transitional metals has been widely recognized [ 3 ]. Due to the high concentration of rosmarinic and caffeic acids, lemon balm may be a more efficient source of antioxidants than other food products, which are present on a market.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported the concentrations of some essential metal ions (iron, copper, and zinc) in the rhizome [ 39 ]. Although these concentrations depend on number of factors (soil composition, environmental pollution, climatic conditions, etc.…”
Section: Chemical Constituents Of Tcr Extractsmentioning
confidence: 99%
“…When plant polyphenols interact with some high-valent metal ions, they can reduce the metal ions from high-valent to low-valent states while complexing them. The complexation of plant polyphenols with metal ions, such as Cu 2+ and Zn 2+ , results in the inhibition of metalloenzymatic activities containing these ions [15]. Our previous study found that in CE, the main antioxidant ingredient is eugenol (58.40%).…”
Section: Introductionmentioning
confidence: 98%